Application of Convex Halbach Array in EDS System - Xiulu ZHANG; Min ZHANG; Weihua MA (机车电传动)
For the insufficient levitation-drag ratio problem of EDS system with traditional rectangular permanent magnet Halbach array, the convex Halbach array with more reasonable magnetic field distribution was adopted for improvement. Firstly, the mechanical properties of EDS system were analyzed theoretically, and the influence of magnetic field distribution on levitation-drag ratio was studied; secondly, the horizontal and vertical components of magnetic field in convex and rectangular Halbach arrays were compared, according to the characteristics of magnetic field distribution of convex array and the theoretical analysis results, the reason why it can optimize levitation-drag ratio was given; finally, the convex Halbach array was applied to the EDS system, the optimization effect of levitation-drag ratio was verified by finite element simulation. The results showed that compared with the traditional rectangular permanent magnet array, convex permanent magnet array could improve the magnetic field and its distribution, which could effectively improve the levitation-drag ratio. The research results can be used to optimize the operation performance of permanent magnet electric maglev train and improve the applicability of permanent magnet electric suspension technology in the field of rail transit.